Subfoveal choroidal thickness in diabetes and diabetic retinopathy - Xu, Jie; Xu, Liang; Du, Kui Fang; Shao, Lei; Chen, Chang Xi; Zhou, Jin Qiong; Wang, Ya Xing; You, Qi Sheng; Jonas, Jost B; Wei, Wen Bin (Ophthalmology (Rochester, Minn.), 2013)
To examine subfoveal choroidal thickness (SFCT) in patients with diabetes mellitus and patients with diabetic retinopathy. Population-based, cross-sectional study. The population-based Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6 ± 9.8 years (range, 50-93 years). A detailed ophthalmic examination was performed including spectral-domain optical coherence tomography (OCT) with enhanced depth imaging for measurement of SFCT and fundus photography for the assessment of diabetic retinopathy. Subfoveal choroidal thickness. Fasting blood samples, fundus photographs, and choroidal OCT images were available for 2041 subjects (58.8%), with 246 subjects (12.1 ± 0.7%) fulfilling the diagnosis of diabetes mellitus and 23 subjects having diabetic retinopathy. Mean SFCT did not differ significantly between patients with diabetes mellitus and nondiabetic subjects (266 ± 108 vs. 261 ± 103 μm; P=0.43) nor between patients with diabetic retinopathy and subjects without retinopathy (249 ± 86 vs. 262 ± 104 μm; P = 0.56). After adjustment for age, sex, axial length, lens thickness, anterior chamber depth, corneal curvature radius, and best-corrected visual acuity, SFCT was associated with a higher glycosylated hemoglobin (HbA1c) value (P<0.001; regression coefficient B, 8.18; 95% confidence interval [CI], 4.02-12.3); standardized coefficient β, 0.08) or with the presence of diabetes mellitus (P = 0.001; B, 21.3; 95% CI, 9.12-33.5) but not with presence of diabetic retinopathy (P = 0.61) or stage of diabetic retinopathy (P = 0.14). As a corollary, after adjusting for age, region of habitation, body mass index, systolic and diastolic blood pressure, and level of education, diabetes mellitus was associated with a thicker SFCT (P<0.001). In contrast, neither presence of diabetic retinopathy (P = 0.61) nor stage of diabetic retinopathy (P = 0.09) were associated significantly with SFCT after adjusting for body mass index, diastolic and systolic blood pressure, and level of education and after adjusting for blood glucose concentrations, HbA1c value, diagnosis of diabetes mellitus, and systolic and diastolic blood pressure, respectively. Patients with diabetes mellitus had a slightly, but statistically significantly, thicker subfoveal choroid, whereas presence and stage of diabetic retinopathy were not associated additionally with an abnormal SFCT. Whereas diabetes mellitus as a systemic disease leads to a slight thickening of the choroid, diabetic retinopathy as an ocular disorder was not associated with choroidal thickness abnormalities after adjusting for the presence of diabetes mellitus. The author(s) have no proprietary or commercial interest in any materials discussed in this article.